VARIACION GEOGRAFICA EN EURYMETOPUM EBURNEOCINCTUM (SPINOLA, 1849) (COLEOPTERA: CLERIDAE), DESCRIPCION DE SUBESPECIES Y CONSIDERACIONES BIOGEOGRAFICAS (Acta Entomológica Chilena, 2022)
The morphologic and chromatic variations in populations of Eurymetopum eburneocinctum(Spinola, 1849) (Coleóptera: Clcridae) is discussed in this paper in 789 samples from Chilcanlocalities dislribuled bclwcen 31°33’ and 46°16' Latitude South.The morphologic analysis considered the last abdominal scgmenls and genital characters of 77males and 58 females; the morphometric evaluation was made on information gathered from 30males and 30 females, considering head width, pronotum width, humeral width, length of pronotumand length of clitra, bcsides total length of individuáis. The statistical trcatmenl included varianceanalysis and discriminan! analysis.Chromatic variations werc performcd through 44 differenl characters in the total samplc, tryinglo evalúate color frequency and estimaling similarity among populations.Four new subspecies are described, i.e., E.e. eburneocinctum, E.e. quinteroensis, E.e.quereoensis, and E.e. elbatoensis, and a biogeographic interpretation of these variations is furtherproposed.